The Economics of producing yellow watermelon irrigated by surface flood irrigation in salamieh area (Journal of Hama University, 2021)
The research aimed to identify the yellow watermelon crop irrigated by drip irrigation method productivity and analyze its revenues in the Salamieh area. Data were collected from a random sample of (50) respondents from some villages in Salamieh district in Hama Governorate. Use the stepwise multivariate regression analysis model, in addition to the tabular presentation of frequency and percentages. The results showed that the average productivity was (2913) kg / dunum. The total cost of yellow watermelon production was (402667) SP / dunum and the average value of the total variable costs of the yellow watermelon crop was (355404) SP / dunum. The total cost of agricultural operations reached (158529) SP / dunum, As for the total value of production requirements, it reached (118467) SP / dunum. As for the fixed costs items, it reached (47263) SP / dunum, as the economic profit reached (226541) SP/dunum،the profitability rate was (%56) and water productivity unit (4.19) kg/m3.